UAS (drone) Arctic Challenges - Next Steps - Kramar, Vadim (Zenodo, 2019)
This paper develops further the overview of technical and operational challenges associated with Unmanned Aerial Systems (UAS) operations in the Arctic. Essentially, many weather-relevant challenges are similar in other climate zones. Due to the lack of research on the Arctic particularities, the overview of included references to generic UAS challenges and considerations. Both collections of challenges, technological and operational, are revised and updated. For most of the listed challenges, the appropriate researches are introduced as entry points to the more specific research areas relevant to the given challenges.